Identification of FGFR4 as a Potential Therapeutic Target for Advanced-Stage High-Grade Serous Ovarian Cancer - Zaid, Tarrik M. (2013)
PURPOSE: To evaluate the prognostic value of fibroblast growth factor receptor 4 (FGFR4) protein expression in patients with advanced-stage, high-grade serous ovarian cancer, delineate the functional role of FGFR4 in ovarian cancer progression, and evaluate the feasibility of targeting FGFR4 in serous ovarian cancer treatment. EXPERIMENTAL DESIGN: Immunolocalization of FGFR4 was performed on 183 ovarian tumor samples. The collected FGFR4 expression data were correlated with overall survival using Kaplan-Meier and Cox regression analyses. The effects of FGFR4 silencing on ovarian cancer cell growth, survival, invasiveness, apoptosis and FGF1-mediated signaling pathway activation were evaluated by transfecting cells with FGFR4-specific small interfering RNAs (siRNAs). An orthotopic mouse model was used to evaluate the effect of injection of FGFR4-specific siRNAs and FGFR4 trap protein encapsulated in nanoliposomes on ovarian tumor growth in vivo. RESULTS: Overexpression of FGFR4 protein was significantly associated with decreased overall survival durations. FGFR4 silencing significantly decreased the proliferation, survival, and invasiveness and increased apoptosis of ovarian cancer cells. Also, downregulation of FGFR4 significantly abrogated the mitogen-activated protein kinase (MAPK), nuclear factor-κB (NFκB), and WNT signaling pathways, which are activated by FGF1. Targeting FGFR4 with the FGFR4-specific siRNAs and FGFR4 trap protein significantly decreased ovarian tumor growth in vivo. CONCLUSIONS: FGFR4 is a prognostic marker for advanced-stage, high-grade serous ovarian carcinoma. Silencing FGFR4 and inhibiting ligand-receptor binding significantly decrease ovarian tumor growth both in vitro and in vivo, suggesting that targeting ovarian cancer cells with high levels of FGFR4 protein expression is a new therapeutic modality for this disease and will improve survival of it.